Access to ICT Services in houses at the Base of the Pyramid in Venezuela (2024)
Objective: The article analyzes whether or not there is an association between the different levels of the BoP and their area of ​​residence with the variables of access to ICT services in a region of Venezuela. Theoretical Framework: The literature review addresses the concepts of access to Information and Communication Technology services, as well as the concept of BoP population. Method: The data analyzed comes from 1,398 households in the Táchira region (Venezuela), which were segmented by poverty conditions, resulting in 675 in the BoP. To establish the association between variables, the Mann Whitney U test was used; The magnitude of the association has been determined using Cramér's V coefficients. Results and Discussion: The results show that access to landline telephone and cable TV services present a moderate association, with respect to socioeconomic levels; while in cell phone service, television ownership and internet service, the association is low. Little interest was evident on the part of public and private organizations in the internet services sector in serving this market segment, as they did not include it in their marketing strategies. Research Implications: These results allow companies in the ICT services sector that have the BoP as a target market to make a distinction in their marketing strategies between the levels of the BoP, since heterogeneity is evident. Originality/Value: The study uses an innovative method of classifying socioeconomic levels that facilitates comparison with other regions by not using income level as the only variable.